Singing complaintes criminelles across Europe - Una McIlvenna (Criminocorpus)
The complainte, a song about crime and punishment, is not simply a French phenomenon, but has been found all over Europe since the early modern period. This article compares the French complaintes of 1870-1940 with their counterparts in English, Italian, German and Dutch to reveal European similarities as well as regional differences. Beginning with a brief discussion of the term ‘complaint’ and its usage in the early modern era, we move into the nineteenth century. Everywhere we find that murder remains the most common subject, but that the numbers of victims are usually much higher in German songs. We find that there are variations in the use of melodies, and that the Italian songs do not use the tradition of contrafactum. The biggest difference is in the printing technologies: the size of the sheets or booklets varies a lot from region to region, and the use of images has seen great changes since the early modern era.